Suppressing the crystallographic disorders induced by excess PbI2 to achieve trade-off between efficiency and stability for PbI2-rich perovskite solar cells. (January 2023) - Zhong, Hua; Liu, Xudong; Liu, Mingxuan; Yin, Song; Jia, Zhongzhong; Fu, Guangsheng; Yang, Shaopeng; Kong, Weiguang
Abstract: Excess PbI2 can improve the efficiency of perovskite solar cells (PSCs). However, it usually leads to poor cell stability due to the chemically active nature of PbI2 . Improving the stability of PbI2 -rich perovskite solar cells without scarifying the efficiency remains challenging. In this work, it is found that the non-uniform and multiple nucleation of perovskite induces crystallographic disorders at grain boundaries (GBs) of PbI2 -rich perovskite. These disorders working as the n-type shallow dopant reduces the energy barrier for photogenerated electrons to reach GBs, triggering the decomposition of excess PbI2 there. Therefore, the instability of PbI2 -rich PSCs is related with the remote coupling of excess PbI2 with the disorders at GBs. In light of this finding, we introduced a small amount (0.5 mol%) of CdI2 into precursor solution to optimize the crystallization of PbI2 -rich perovskite, and finally achieved a trade-off between efficiency and stability in PbI2 -rich PSCs. The optimized PSCs with 10 mol% excess PbI2 (PC-Device) achieved a champion efficiency of 24.26% at the bandgap 1.55 eV with robust stability. PC-Devices maintain more than 90% of the initial efficiency after being stressed under UV light in ambient with a relative humidity of 50% for 500 h, and 70% under heat at 85˚C for 400 h, both of which are far superior to the pristine PbI2 -rich solar cells. Graphical Abstract: ga1 Highlights: The instability of PbI2 -rich PSCs is related to the disorders at GBs of perovskite. A small amount of CdI2 is introduced to restrain the disorders at GBs of perovskite with excess PbI2 . The stability of PbI2 -rich PSCs is promoted greatly with the assist of CdI2 . High efficiency (24.26%) and Voc (1.18 V) are achieved for FAMA mixed PSCs.